2017
DOI: 10.1007/s41062-017-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of the causes of the major landslide of Bukit Antarabangsa in 2008 using fault tree analysis

Abstract: human errors which occur either as a result of negligence or as a result of several types of uncertainties. In this context, this study suggests a theoretical framework to address human errors and to mitigate the chances of slope failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The increase in soil water weight with heavy rainfall or rapid snowmelt, but also with leaking water pipes, canals, irrigation systems, reservoirs, and septic tanks, and rising groundwater table is sometimes mentioned as (e.g., Selby, 1993), or proved to be (Kazmi et al, 2017), a cause of slope (over)loading. However, one commonly considers that the main effect of elevation of the water table is an increase in pore pressure that proportionately decreases the strength of the slope material, thus tending to trigger landslides (e.g., Wieczorek, 1996).…”
Section: Overloading By High Soil Water Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in soil water weight with heavy rainfall or rapid snowmelt, but also with leaking water pipes, canals, irrigation systems, reservoirs, and septic tanks, and rising groundwater table is sometimes mentioned as (e.g., Selby, 1993), or proved to be (Kazmi et al, 2017), a cause of slope (over)loading. However, one commonly considers that the main effect of elevation of the water table is an increase in pore pressure that proportionately decreases the strength of the slope material, thus tending to trigger landslides (e.g., Wieczorek, 1996).…”
Section: Overloading By High Soil Water Contentmentioning
confidence: 99%
“…Beside waste, voluminous landfill is also more and more involved in construction works, e.g., for highway or railway embankments. Finally, anthropogenic loading eventually leading to unexpected slope failure may also be caused by water accumulating in the slope material due to leakage or burst of pipes and septic tanks, or infiltration from canals, or intensive irrigation of cropland, with the common twofold impact on slopes of added weight and increased pore pressure (e.g., Kazmi et al, 2017).…”
Section: (Local) Overloading By Fills and Heavy Constructionsmentioning
confidence: 99%
“…It was discovered that 24 locations from Hulu Kelang soil slope region [11]. The major landslides of Highland Tower have been observed that it caused by the leakage of pipe under the ground [12]. However, the further question is whether the main problems of pipe leakage are the main cause of all the landslides in Hulu Kelang region.…”
Section: Location Of Studymentioning
confidence: 99%
“…The soil used in this study was obtained from Bukit Antarabangsa, Selangor, Malaysia (3.1862° North and 101.7704° East). Bukit Antarabangsa sits within the landslide-prone region of Ulu Klang whereby a prominent landslide occurred in 2008 which resulted in casualties and heavy damages [27]. The residual soil from this location was chosen due to the historical records of slope failure incidents that make Bukit Antarabangsa a critical area that is highly susceptible to acid rain-induced slope failure, therefore, warranting urgent remedial and corrective measures if acid rain is a reason for concern to prevent a recurrence of the 2008 fatal landslide.…”
Section: Soil Propertiesmentioning
confidence: 99%